The Aftermath of Pulmonary Embolism: Are Residual Thrombi Clinically Significant? - Irina Pocienė; Edvardas Danila (Diagnostics)
Background: Following acute pulmonary embolism (PE), disease outcomes vary among patients. Complete recovery occurs in some cases, while others may experience persistent long-term symptoms, disease recurrence, or progression to chronic thromboembolic pulmonary hypertension (CTEPH). The exact reasons behind incomplete recovery and different outcomes are still not well established. This review aims to present the existing data regarding the clinical significance of residual thrombi after acute PE, particularly in the context of disease recurrence, the development of CTEPH, or persistent symptoms and functional limitations. Methods: Original articles, systematic reviews, and meta-analyses relevant to the topic are reviewed. Results: Incomplete thrombus resolution after acute PE is quite common, with studies showing that it affects one-fourth to one-third of PE patients, despite receiving optimal anticoagulant treatment. It has been shown that residual thrombi after acute PE play a role in the risk of PE recurrence. However, there is still no standardized method to differentiate disease recurrence from residual thrombi in pulmonary imaging studies, particularly in cases where no follow-up scans and different imaging techniques are used for thrombi detection. Residual vascular obstruction is necessary for the development of CTEPH. Evidence suggests that the extent of residual thrombi contributes to a higher risk of CTEPH. Still, there is a need to standardize both the timing of residual thrombi assessment and the evaluation of their distribution, in relation to the development of CTEPH. The significance of residual thrombi for persistent symptoms and functional limitation remains debatable. Research indicates that nearly half of patients experience long-term symptoms after acute PE. Still, it is believed that these symptoms are not necessarily caused only by residual thrombi, but rather by the worsening of other comorbid conditions. Conclusions: Studies show that residual thrombi after acute PE are significant for PE outcomes. It may be beneficial to consider evaluating residual pulmonary vascular obstruction when treating patients after acute PE to optimize the duration of anticoagulant therapy and improve patient outcomes.